Intracerebral haemorrhage volume, haematoma expansion and 3-month outcomes in patients on antiplatelets. A systematic review and meta-analysis. - Goeldlin, Martina B.; Siepen, Bernhard M.; Mueller, Madlaine; Volbers, Bastian; Z'Graggen, Werner; Bervini, David; Raabe, Andreas; Sprigg, Nikola; Fischer, Urs; Seiffge, David J. (European Stroke Journal, 2021)
AIMS: We assessed the association of prior antiplatelet therapy (APT) at onset of intracerebral haemorrhage (ICH) with haematoma characteristics and outcome. METHODS: We performed a systematic review and meta-analysis of studies comparing ICH outcomes of patients on APT (APT-ICH) with patients not taking APT (non-APT-ICH). Primary outcomes were haematoma volume (mean difference and 95% CI), haematoma expansion (HE), in-hospital 3-month mortality rates and good functional outcome (modified Rankin Scale score 0-2). We provide odds ratios (ORs) from random effects models and subgroup analyses for haematoma expansion and short-term mortality rates. RESULTS: We included 23 of 1551 studies on 30,949 patients with APT-ICH and 62,018 with non-APT-ICH. Patients on APT were older (Δmean 6.27 years, 95% CI 5.44-7.10), had larger haematoma volume (Δmean 5.74 mL, 95% CI 1.93-9.54), higher short-term mortality rates (OR 1.44, 95% CI 1.14-1.82), 3-month mortality rates (OR 1.58, 95% CI 1.14-2.19) and lower probability of good functional outcome (OR 0.61, 95% CI 0.49-0.77). While there was no difference in HE in the overall analysis (OR 1.32, 95% CI 0.85-2.06), HE occurred more frequently when assessed within 24 h (OR 2.58, 95% CI 1.18-5.67). We found insufficient data for comparison of single versus dual APT-ICH. Heterogeneity was substantial amongst studies. DISCUSSION: APT is associated with larger baseline haematoma volume, early (<24 h) haematoma expansion, mortality rates and morbidity in patients with ICH. Data on differences in single and dual APT-ICH are scarce and warrant further investigation. New treatment options for APT-ICH are urgently needed.
EVALuna2:527467